Encountering the Sacred in Psychotherapy: How to Talk with People About Their Spiritual Lives - Grainger, Roger (Implicit religion, 2005)
The article reviews the book "Encountering the Sacred in Psychotherapy: How to Talk with People About Their Spiritual Lives," by James L. Griffith and Melissa E. Griffith.